The Decline of Democracy and Parliaments in Eastern Central Europe: A Case Study on Poland - Fadhlia, Maudy Noor; Makanbaeva, Akbermet (Green Publisher Indonesia, 2023)
The parliamentary system in Eastern Central Europe has been known for its authoritarianism, with parliaments being subordinated to communist leadership and parties, as seen in Poland. The decline of democracy in Poland reached its peak when the conservative party was in power, controlling the legislative and judiciary in this former communist country. Corruption and social inequality threatened modern democracy, leading to protests and criticism from the people. The ruling party mainly focused on economic and political power in the name of citizens, leading to criticism even from the media. The study aims to examine the decline of democracy and parliaments in eastern central Europe in Poland. The study uses a case study and qualitative approach to identify the factors behind the decline of democracy in Poland. The main issues were the credibility of state institutions and the lack of media freedom, in addition to corruption. The political change in Poland and increasing populism led to the decline of democracy, which continued to receive criticism even from the media.